2005
DOI: 10.1111/j.1533-8525.2005.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Home-to-Job and Job-to-Home Spillover: The Impact of Company Policies and Workplace Culture

Abstract: We draw on gender theory and neo-institutional theory to examine the impact of workplace characteristics and family demands on negative job-to-home and home-to-job spillover. Our multivariate analyses of the 1997 National Study of the Changing Workforce data indicate that familysupportive workplace cultures reduce negative spillover in both directions, whereas the availability of company policies, such as dependent care benefits and flextime, do not. Our results also show that family demands increase spillover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
207
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(217 citation statements)
references
References 73 publications
5
207
2
2
Order By: Relevance
“…Vivid imagery of human beings in need can trigger the visceral responses and physiological arousal in observers that are the precursors to the empathic urge to help (Arnold, 1960;Hendriks & Vingerhoets, 2006;Loewenstein, 1996;Maitlis & Sonenshein, 2010;Marsh & Ambady, 2007), as demonstrated in research on donations in response to the 2004 South Asian tsunami (Smith & McSweeny, 2007) and the 2001 "9/11" attacks (Piferi, Jobe, & Jones, 2006). In the context of our theorizing, we propose that by altering perceptions of proximity to those in need, vividness affects whether the empathyevoking properties of that need arouse empathy in the workplace irrespective of the human need's relevance for the organization or workplace functioning Judge & Ilies, 2004;Mennino, Rubin, & Brayfield, 2005;Rothbard, 2001 Centrality of moral identity. In addition to the perceived features of the need itself, individual dispositional characteristics also influence the intensity of empathic arousal.…”
Section: A Model Of Collective Empathy In Corporate Philanthropy Decimentioning
confidence: 99%
“…Vivid imagery of human beings in need can trigger the visceral responses and physiological arousal in observers that are the precursors to the empathic urge to help (Arnold, 1960;Hendriks & Vingerhoets, 2006;Loewenstein, 1996;Maitlis & Sonenshein, 2010;Marsh & Ambady, 2007), as demonstrated in research on donations in response to the 2004 South Asian tsunami (Smith & McSweeny, 2007) and the 2001 "9/11" attacks (Piferi, Jobe, & Jones, 2006). In the context of our theorizing, we propose that by altering perceptions of proximity to those in need, vividness affects whether the empathyevoking properties of that need arouse empathy in the workplace irrespective of the human need's relevance for the organization or workplace functioning Judge & Ilies, 2004;Mennino, Rubin, & Brayfield, 2005;Rothbard, 2001 Centrality of moral identity. In addition to the perceived features of the need itself, individual dispositional characteristics also influence the intensity of empathic arousal.…”
Section: A Model Of Collective Empathy In Corporate Philanthropy Decimentioning
confidence: 99%
“…When the boundary between the two domains of work and home are weakened, work seeps into home, and home seeps into work. This can have negative consequences, such as when there is conflict between the demands of work and home (Small & Riley, 1990), or when employees are trying to balance competing roles (Mennino et al, 2005;Schieman et al, 2003). To prevent these negative effects from occurring, employees can strengthen their boundaries, thus making the demarcation between work and home clear -with positive outcomes, such as increased job satisfaction and lower burnout (Bulger et al, 2007).…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…Although this spillover can be positive at times, researchers have primarily been concerned with negative spillover that occurs when the demands of work and home compete for employees' time, energy, and attention (Small & Riley, 1990). Trying to balance competing roles between work and home can lead to negative wellbeing (Mennino, Rubin, & Brayfield, 2005;Schieman, McBrier, & Gundy, 2003). Far from being passive recipients of such conflicts, however, employees can engage in boundary work that seeks to strengthen the demarcation between work and home, ultimately leading to positive outcomes (Bulger, Matthews, & Hoffman, 2007).…”
Section: Commuting As a Rite Of Crossing Role Boundariesmentioning
confidence: 99%
“…The study conducted by Mennino et al [1] showed that different demographic variables might have different impacts on spillover. Due to different demographic variables, it is of interest to assess how nurses perceive in work-life balance in terms of seven questions in burnout dimension by using independent sample t test for mean differences and one-way analysis of variance (ANOVA).…”
Section: Introductionmentioning
confidence: 99%
“…Mennino et al [1] stated that the atmosphere of the workplace (culture) is an important factor to result in negative spillover in both home-to-job and job-to-home directions. The negative spillover indicates there is a work-family conflict.…”
Section: Introductionmentioning
confidence: 99%